Glioblastoma multiforme: a case report - Eliecer A. Figueroa Verdecia; Agustín Arocha García; Daylanis V. Figueroa Verdecia (Acta Médica del Centro, 2010)
The astrocytic tumors are the most frequent gliomas reported in different studies. They are subdivided in well-differentiated astrocytomas (Grade II), anaplastic astrocytomas (Grade III) and glioblastoma multiforme (Grade IV). These categories represent a spectrum in relation to the prognosis and its potential growth (the degree of nuclear atypia, cellularity, mitosis and vascular changes). A 74-year old white male patient with a diagnosis of glioblastoma multiforme, who is treated at the Arnaldo Milian Provincial University Hospital, is presented in this article.